Clinical and endoscopical and morphofunctional scores in evaluation of development of gastroesophageal reflux disease in various age groups - M. A. Osadchuk; A. M. Zolotovitskaya; N. V. Kireyeva; S. N. Nikolenko; I. M. Kvetnoy (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To develop diagnostic and prognostic criteria of gastroesophageal reflux disease (GERD) at patients of various age groups on the basis of analysis of clinical and endoscopical, functional and morphological data.Material and methods. Overall 170 patients with GERD were included in original investigation, of them were of 90 young age (18–23 years) and 80 medium age groups (45–59 years). Patients with chronic H. pyloriassociated gastritis were included to control groups (30 young age, 20 medium age group) and 15 generally healthy patients of young age.Results. Chronic gastritis and duodenitis were revealed in majority of GERD patients: in patients of young age superficial gastritis prevails; in medium age group gastroesophageal reflux was associated with gastritis accompanying with signs of atrophy. In development of the catarrhal form of GERD in patients of young age it is possible to consider following basic pathogenic factors: chronic H. pylori-associated gastritis; lower esophageal sphincter incompetence closely related to nutritional deficiency; long-term exposure to acidic gastric contents at gastroesophageal reflux due to disorders of motor function of the esophagus on a background of hyperplasia of NO-synthase and endothelin-1-producing stomach cells. The catarrhal form of GERD at middle-aged patients develops on a background of gastritis with signs of atrophy, associated to H. pylori infection, contaminations of distal esophagus by H. pylori and foci of gastric metaplasia, dysfunction of motility of upper regions of the gut on a background of hyperplasia of NO-synthase and endothelin-1-producing cells of the esophagus and the stomach. At the erosive form of GERD same ethipathogenic factors take place, as at the catarrhal form. However, disorder of neurohumoral regulation and pathological acid production, exhausting compensatory potential of the body, play the leading role. It results in more severe damage of esophageal mucosa with development of erosive esophagitis and extraesophageal manifestations. Assessment of patients with erosive form of GERD at endoscopic control during treatment revealed, that epithelialisation of esophageal erosions in medium age group took significantly longer time, than at young patients. GERD develops on a background of significant atrophic and inflammatory changes of gastric mucosa. Changes of antral region initiate and maintain desynchronization in functioning of the lower esophageal sphincter, being the leading cause of GERD.Conclusions. Published studies indicate that GERD is the disease with primary defect of motor control of gastro-intestinal tract. Its development at patients of all age groups is observed on a background of gastritis with, probably, genetically determined hyperplasia of gastric epithelial cells producing NO-synthase and endothelin-1. Hyperproduction of nitric oxide and endothelin-1 in the stomach antrum causes preconditions for development of motor disorders and reflux that, in turn, lead to inflammatory and dystrophic changes in the esophagus. Thus in age aspect these disorders aggravate and total disturbance of neurohumoral regulation of the upper parts of the gut that determines extraesophageal manifestations of GERD is observed. This provides negative effect on terms of esophageal erosions healing.